A study of the incidence of malignancy and clinicopathological correlation of incidence of malignancy in peptic perforation disease - Chatterjee, Jishnu; Singh, Manju; Shrimor, Prachi; Chandrakar, Jayanti (International Surgery Journal, 2025)
Background: Gastrointestinal perforation, a common emergency in surgery, often results from peptic ulcer disease but can also be caused by gastric cancer. Peptic ulcers, with a lifetime risk of 10%, are more prevalent in developing countries and linked to factors like H. pylori infection, NSAID use, smoking, and stress. Complications include bleeding, perforation, obstruction, and cancer. Perforation leads to peritonitis, requiring treatment via perforation closure. Although gastric cancer accounts for 10-16% of perforations, many patients don’t undergo post-operative biopsy, potentially missing cancer diagnoses. This study aimed to determine the true incidence of malignancy in perforation cases as well as in specific demographics and identify contributing factors. Methods: The present study was aimed at determining the true incidence of malignancy in perforation cases as well as in specific demographics and identify contributing factors. Biopsies taken from the margins of gastric (antral) perforation during the operation, were subjected to histopathological examination. Results: Our study found only 1 case of perforation in a male patient, in the 61-70-year age bracket with history of both smoking as well as alcohol, to have an associated malignancy. Conclusions: The incidence of malignancy in gastric perforation is very low and as a result, often goes undiagnosed, resulting in lack of appropriate treatment of the underlying cancer.